SUMBANGAN BAHASA ARAB TERHADAP BAHASA INDONESIA DALAM PERSPEKTIF PENGEMBANGAN BAHASA DAN BUDAYA - Tajudin Nur (Humaniora, 2014)
This study discusses the Arabic contributions to the Bahasa Indonesia in the perspective of language and culture developments. The data are taken from Big Indonesian Dictionary (KBBI). Based on the analysis done shows that there are three important aspects of the Arabic contribution to the Bahasa Indonesia, namely vocabulary enrichment, grammar system, and cultural development. In the aspect of vocabulary enrichment, approximately 2.336 Arabic vocabularies have moved into Bahasa Indonesia. In the aspect of grammar, the Arabic grammatical system is used in the grammatical system of Bahasa Indonesian such as gender formation and formation of word that shows the meaning of nature. In the cultural aspect, the Arabic language also contribute to the development of Indonesian culture, such as the use of proper names in Arabic by the Indonesian Muslims, religious institutions, and state. Moreover, the Arabic terms are also used in everyday expressions, literature, and in the constitutional system of the Republic of Indonesia.